Ancient magic artefacts and people: interpreting symbols, tracking personal experiences in Greek archaeological museums - Mouliou, Marlen (Journal of Greek Archaeology, 2017)
In addition to the basic existential issues related to lived human experience, such as life, death, peace, war, love and memory, something that unites people through the ages is the desire to attract good fortune or repel the bad, resulting in superstitions and practices related to the mysterious power of ‘magic’ and its impact on human beings.